Representasi keterampilan menulis akademis dalam laporan akhir mahasiswa studi independen bersertifikat e-commerce (Analisis sistem transitivitas) - Dani, Meri Septi Putri; Leiliyanti, Eva; Ansoriyah, Siti (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to reveal the representation of academic writing skills among students of the Studi Independen Bersertifikat (SIB) E-Commerce through an analysis of the transitivity system in their final reports. The analysis focuses on the types of processes present in the reports, including material, mental, relational (attributive and identifying), verbal, existential, and behavioral processes. This study employs a qualitative-descriptive research design. The data source consists of academic texts in the form of final reports written by ten students or participants of SIB E-Commerce from batch 1 to batch 3 (2021—2023). The findings indicate that material processes are the most dominantly used by the students, followed by relational attributive, relational identifying, and mental processes. Meanwhile, the use of existential and verbal processes is relatively limited, and behavioral processes are absent. The dominance of material processes suggests that students represent their experiences by describing physical activities or concrete actions undertaken during the program. This reflects the students’ tendency to narrate their knowledge and practical experiences through concrete descriptions of activities.